2012
DOI: 10.1029/2012sw000785
|View full text |Cite
|
Sign up to set email alerts
|

Wp index: A new substorm index derived from high‐resolution geomagnetic field data at low latitude

Abstract: [1] Geomagnetic field data with high time resolution (typically 1 s) have recently become more commonly acquired by ground stations. Such high time resolution data enable identifying Pi2 pulsations which have periods of 40-150 s and irregular (damped) waveforms. It is well-known that pulsations of this type are clearly observed at mid-and low-latitude ground stations on the nightside at substorm onset. Therefore, with 1-s data from multiple stations distributed in longitude around the Earth's circumference, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 49 publications
2
61
0
1
Order By: Relevance
“…Figure shows the AL , W p , and D s t indices for 11–16 November 2012. The W p index reflects Pi2 wave power at low latitude on the nightside and is useful for identifying substorm onset [ Nosé et al , ]. The 7 h intervals of observations by Probe A and Probe B that are used in the present study are indicated by red and blue horizontal thick bars, respectively.…”
Section: Observations Of Oxygen Torus: 15 November 2012 Eventmentioning
confidence: 99%
“…Figure shows the AL , W p , and D s t indices for 11–16 November 2012. The W p index reflects Pi2 wave power at low latitude on the nightside and is useful for identifying substorm onset [ Nosé et al , ]. The 7 h intervals of observations by Probe A and Probe B that are used in the present study are indicated by red and blue horizontal thick bars, respectively.…”
Section: Observations Of Oxygen Torus: 15 November 2012 Eventmentioning
confidence: 99%
“…To confirm Pi2 and its association with substorm activity, we further looked into the AL and Wp indices. Wp (Wave and planetary) is a substorm index developed by Nose et al [2012] which reflects the Pi2 power at low latitude. It is considered as a useful indicator of substorm onset.…”
Section: 1002/2014ja020958mentioning
confidence: 99%
“…AL and Wp indices together provide the evidence of substorm activity and associated Pi2 oscillations at low latitude. Wp index being sensitive to the onset of even smaller substorms in comparison to AL [Nose et al, 2009], we have chosen Wp (≥0.5) as the primary criterion for selecting Pi2 events. AL and Wp values are obtained from World Data Center (WDC), Kyoto, web page.…”
Section: 1002/2014ja020958mentioning
confidence: 99%
“…As an alternative to the traditional Dst index (Sugiura, 1964), new indexes were developed using DWT, such as the wavelet-based index of storm activity (WISA; Jach et al, 2006;Xu et al, 2008) and Wp (Nosé et al, 2012), among others. Motivated by the works of Mendes et al (2005), Mendes da Costa et al (2011), Hafez et al (2013) and Klausner et al (2014aKlausner et al ( , b, 2016a, which use the DWT to detect transition regions and to localize singularities in geophysical data, in this work, the geomagnetic variation associated with the events of CIRs and HSSs in 2007 will be analyzed.…”
Section: Klausner Et Al: Analysis To Identify Local Geomagneticalmentioning
confidence: 99%